Complications Of Cataract Surgery In Rural Eye Camps And Their Burden On Tertiary Health Care Facility - Rafi, Piya Muhammad Musammat; Khan, Muhammad Rizwan; Zubair, Maria; Hussain, Majid; Muneeb, Muhammad; Rasool, Wajeeha (Journal of Rawalpindi Medical College, 2025)
Objective: To Document and Elaborate Complications of cataract surgery in rural eye camps and their burden on tertiary health care facility. MATERIAL AND METHODS: For this noncomparative, descriptive cross-sectional study, data was collected Retrospectively. All patients who presented in the ophthalmology outpatient department(opd), Bahawal Victoria Hospital Bahawalpur and fulfilled the inclusion criteria were included in the study. The strategy of non-probability purposive sampling was adopted. RESULTS: Data from a total of 200 patients were included in the study who presented in eye opd with severe ocular morbidity after camp eye surgery. Of the total, 91(45.5%) were male and 109 (54.5%) were female patients. Of all the complications; significant refractive errors, (refractive errors that compel the patients to attend eye opd) were in greatest numbers, 56 (28%). Next were the patients with Corneal oedema 50 (25%). 42 (21%) patients present with posterior segment diseases and Endophthalmitis occurred in 39(19.5%). Posterior Capsule rupture was present in 33(16.5%) and IOL dislocation /Lens fragments, each, were present in 27(13.5%). 25(12.5%) patients were Aphakic while 15(7.5%) patients present with Retinal detachment. CONCLUSION: There is a need for an improvement in the quality of surgery with a more balanced distribution of services and highly skilled surgeons should operate in eye camps. The standard surgical protocol should be followed for camp surgery. Unethical practices should be strictly discouraged at all levels. Key Words: Cataract surgery, Healthcare facility, Endophthalmitis, Corneal oedema, Refractive errors, Postoperative Complications.